Religion, synchrony, and cooperation - Cohen, Emma (Religion, brain & behavior, 2014)
Shared beliefs about supernatural agents and joint engagement in ritual activities are often proposed to engender cohesion and cooperation within religious communities. We report the results of an experiment that investigated the effects of religious-concept priming and synchronous activity among Brazilian drummers. Participants were divided into two between-subjects narrative priming conditions: religious and secular. Within each priming condition, we applied a within-subjects design to investigate effects of solo, group synchronous, and group non-synchronous drumming on endorphin release and cooperation. We found an effect of priming conditions, such that there was a trend toward higher cooperation in the religiously primed group compared to the secularly primed group. We found neither a main effect of the drumming condition nor a drumming-priming interaction effect. Results suggest that behavioral synchrony alone is insufficient to increase cooperation. In light of previous findings, we propose that high levels of physical exertion or social-cognitive mechanisms, such as overlapping task-representation or intentional coordination, are also required for cooperation.